2005
DOI: 10.1111/j.1600-0765.2005.00787.x
|View full text |Cite
|
Sign up to set email alerts
|

Protective effects of etoricoxib, a selective inhibitor of cyclooxygenase‐2, in experimental periodontitis in rats

Abstract: These data provide evidence that systemic therapy with etoricoxib can retard alveolar bone loss in a ligature-induced periodontitis model in rats.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
41
1
10

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(55 citation statements)
references
References 17 publications
3
41
1
10
Order By: Relevance
“…We used a delayed treatment model starting 5 days after the induction of periodontitis, when bone loss is already demonstrable (30). This approach more closely resembles the situation in clinical outpatient practice rather than an early treatment (18).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We used a delayed treatment model starting 5 days after the induction of periodontitis, when bone loss is already demonstrable (30). This approach more closely resembles the situation in clinical outpatient practice rather than an early treatment (18).…”
Section: Discussionmentioning
confidence: 99%
“…A recent study has documented a preventive benefit of etoricoxib (18). However, the mode of treatment with etoricoxib, a selective COX-2 inhibitor, has been poorly studied in periodontal disease models.…”
Section: Introductionmentioning
confidence: 99%
“…Stereomicroscopic evaluation (Olympus SZ-PT, Tokyo, Japan) confirmed these observations; the maxillae were photographed (Olympus C-4000 ZOOM, Tokyo, Japan) under the stereomicroscope and are shown in Figure 1A. The present study employed the direct digital radiography method (22,23; Figure 1B). The stereomicroscopic and digital radiographic evaluations were conducted only to evidence the periodontal breakdown.…”
Section: Determination Of the Presence Of Periodontitismentioning
confidence: 79%
“…(16) Other investigators have conducted experiments over much longer periods of time. (17) Fernandeset al (18) compared the histometric and morphometric methods and found that both are capable of detecting alveolar bone loss in rats. Li and Amar (19) likewise compared the different methods-morphometric isolated, histometric and morphometric associated and micro-computed tomography-in 100 male rats, and their findings showed that all the methods are accurate for quantification of alveolar bone loss (20) .The histological results of the present study revealed that in control ligature group lack of normal architechture of periodontal ligament (PDL), resorptive bays on bone detachment associatedwith PDL detachment in certain areas, In vehicle group, total degeneration of PDL, lack of normal architecture of PDL and resorptive bone area, Using watery extract of lepiduimsativum, at 15 days there were gradual healing of PDL with marked reduction in marrow spaces numbers, completebone attachment, while in 30 days, almost complete regeneration of PDL and reversal lines are observed.…”
Section: Discussionmentioning
confidence: 99%